Effect of Support on Catalytic Efficiency of Au-Pd Bimetallic Catalysts: Effect of Support on Heterogeneous Catalysis - Sajjad, Noreen; Sultan, Ayesha; Rubab, Syeda Laila; Batool, Fozia; Zuber, Muhamamd; Saeed, Shagufta; Hussain, Ghulam; Acevedo, Roberto (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2021)
The supported Au-Pd based bimetallic catalysts nanomaterials have attracted mounting research attention for applications in diverse fields of pharmaceutical, fragrance industry and nanotechnology. In the present study, we have undertaken a detailed investigation on synthesis and catalytic activity studies for selective oxidation of benzyl alcohol by various Au-Pd supported catalysts on different supports & with different metal ratios. The support systems were prepared by simple physical grinding protocol. The catalytic performance of supported bimetallic catalysts was evaluated on the basis of selectivity and TOF. The results of this study confirm that efficiency of catalysts is highly dependent on the nature of the support and also dependent on metal ratios.